Intra thoracic migration of ureteric stent after exstrophy bladder closure: Unusual complication - Shasanka Shekhar Panda; Minu Bajpai; Amit Singh; Karunesh Chand (Wolters Kluwer Medknow Publications, 2015)
Classic bladder exstrophy is a rare malformation of the genitourinary tract requiring surgical intervention either one-staged or staged fashion. Premature stent dislodgement is a well-known reported complication. We are reporting an unusual case of migration of ureteric stent to thoracic cavity leading to the pleural effusion and respiratory distress in early post-operative period.